Perceptions of healthcare professionals regarding their own body weight in selected public hospitals in Mpumalanga Province, South Africa - M C Phetla; L Skaal (South African Medical Association, 2017)
Background. Obesity has been cited as a public health problem in both developing and developed countries. There is evidence that rates of obesity have increased among healthcare workers (HCWs) in South Africa (SA), especially those who do night shifts, with a negative effect on health. Perceptions of body weight contribute significantly to the desire to lose weight or not to do so. Objective. To determine perceptions of HCWs regarding their own body weight in selected public hospitals in Mpumalanga Province, SA. Methods. The study design was a cross-sectional survey. A total of 210 HCWs were sampled. Data were collected using self-administered questionnaires. Anthropometric measurements such as weight and height were objectively measured and body mass indices (BMIs) were calculated. Results. Of the sample of HCWs 82.4% were females, with a mean age of 37.8 years. About half (51.9%) were obese and 21.4% were overweight. They tended to misperceive their body weight compared with actual BMI classification, with the majority of obese and overweight individuals considering themselves to be of normal weight. Conclusions. The results indicate that HCWs misclassify their own body weight, which is a risk factor for obesity. It is important to focus on the health of this group of workers, on whom the health of South Africans depends and who should be the drivers of healthy living for all. Correct classification of their own body weight will encourage people to take action in a bid to combat their own and others' obesity.